FAPI PET/CT in the Diagnosis of Abdominal and Pelvic Tumors - Yang, Tianshuo; Ma, Long; Hou, Haodong; Gao, Feng; Tao, Weijing (Frontiers in Oncology, 2022)
Positron emission tomography/computed tomography (PET/CT) with 18F-fluorodeoxyglucose (18F-FDG) is currently a standard imaging examination used in clinical practice, and plays an essential role in preoperative systemic evaluation and tumour staging in patients with tumours. However, 18F-FDG PET/CT has certain limitations in imaging of some tumours, like gastric mucus adenocarcinoma, highly differentiated hepatocellular carcinoma, renal cell carcinoma, and peritoneal metastasis. Therefore, to search for new tumour diagnosis methods has always been an important topic in radiographic imaging research. Fibroblast activation protein (FAP) is highly expressed in many epithelial carcinomas, and various isotope-labelled fibroblast activation protein inhibitors (FAPI) show lower uptake in the brain and abdominal tissues than in tumour, thus achieving high image contrast and good tumour delineation. In addition to primary tumours, FAPI PET/CT is better than FDG PET/CT for detecting lymph nodes and metastases. Additionally, the highly selective tumour uptake of FAPI may open up new application areas for the non-invasive characterization, staging of tumours, as well as monitoring tumour treatment efficacy. This review focuses on the recent research progress of FAPI PET/CT in the application to abdominal and pelvic tumours, with the aim of providing new insights for diagnostic strategies for tumour patients, especially those with metastases.